STRATEGI PENCEGAHAN DAN PENANGANAN POLITIK UANG DALAM PENYELENGGARAAN PEMILU SERENTAK DI INDONESIA - Puannandini, Dewi Asri; Urpiah, Sani (Universitas Ekasakti, 2023)
Money politics is a serious problem in the implementation of elections in Indonesia. Currently money politics has become a culture and commonplace in the eyes of the Indonesian people, so that people have no fear of practicing money politics, either by giving rewards or receiving certain rewards by the candidates. The practice of money politics must be prevented in order to create a good, transparent and accountable democratic system. This research is a normative juridical research. The approaches used in this study include a conceptual approach, a statutory approach, and a case approach. Sources of data obtained from primary and secondary data sources. From the results of the study it was found that the factors for the occurrence of money politics include: first, People's views that are used to money politics in elections, second, money politics become a bad culture every Indonesian election, third, weak law enforcement in Indonesia, fourth, weak faith factor, fifth, poverty factor. Sixth, the lack of public understanding of politics and the impact of money politics. The prevention efforts include: the establishment of an electoral justice system (EJS), providing understanding to the public about politics and the impact of money politics, and eradicating poverty in various sectors. Strengthen law enforcement and regulations as well as sanctions both criminal and administrative to deter perpetrators of money politics. lack of public understanding of politics and the impact of money politics.